Comparative transcriptomics identifies the key in planta-expressed genes of Fusarium graminearum during infection of wheat varieties - Tu, Qiang; Wang, Lirong; An, Qi; Shuai, Jie; Xia, Xiaobo; Dong, Yifan; Zhang, Xu; Li, Gang; He, Yi (Frontiers in Genetics, 2023)
Fusarium head blight (FHB), caused mainly by the fungus Fusarium graminearum, is one of the most devastating diseases in wheat, which reduces the yield and quality of grain. F. graminearum infection of wheat cells triggers dynamic changes of gene expression in both F. graminearum and wheat, leading to molecular interactions between pathogen and host. The wheat plant in turn activates immune signaling or host defense pathways against FHB. However, the mechanisms by which F. graminearum infects wheat varieties with different levels of host resistance are largely limited. In this study, we conducted a comparative analysis of the F. graminearum transcriptome in planta during the infection of susceptible and resistant wheat varieties at three timepoints. A total of 6,106 F. graminearum genes including those functioning in cell wall degradation, synthesis of secondary metabolites, virulence, and pathogenicity were identified during the infection of different hosts, which were regulated by hosts with different genetic backgrounds. Genes enriched with metabolism of host cell wall components and defense response processes were specifically dynamic during the infection with different hosts. Our study also identified F. graminearum genes that were specifically suppressed by signals derived from the resistant plant host. These genes may represent direct targets of the plant defense against infection by this fungus. Briefly, we generated databases of in planta-expressed genes of F. graminearum during infection of two different FHB resistance level wheat varieties, highlighted their dynamic expression patterns and functions of virulence, invasion, defense response, metabolism, and effector signaling, providing valuable insight into the interactions between F. graminearum and susceptible/resistant wheat varieties.